Pharmacokinetics of quinine, chloroquine and amodiaquine. Clinical implications. - Krishna, S; White, N (1996)
Malaria is associated with a reduction in the systemic clearance and apparent volume of distribution of the cinchona alkaloids; this reduction is proportional to the disease severity. There is increased plasma protein binding, predominantly to alpha 1-acid glycoprotein, and elimination half-lives (in healthy adults quinine t1/2z = 11 hours, quinidine t1/2z = 8 hours) are prolonged by 50%. Systemic clearance is predominantly by hepatic biotransformation to more polar metabolites (quinine 80%, quinidine 65%) and the remaining drug is eliminated unchanged by the kidney. Quinine is well absorbed by mouth or following intramuscular injection even in severe cases of malaria (estimated bioavailability more than 85%). Quinine and chloroquine may cause potentially lethal hypotension if given by intravenous injection. Chloroquine is extensively distributed with an enormous total apparent volume of distribution (Vd) more than 100 L/kg, and a terminal elimination half-life of 1 to 2 months. As a consequence, distribution rather than elimination processes determine the blood concentration profile of chloroquine in patients with acute malaria. Parenteral chloroquine should be given either by continuous intravenous infusion, or by frequent intramuscular or subcutaneous injections of relatively small doses. Oral bioavailability exceeds 75%. Amodiaquine is a pro-drug for the active antimalarial metabolite desethylamodiaquine. Its pharmacokinetic properties are similar to these of chloroquine although the Vd is smaller (17 to 34 L/kg) and the terminal elimination half-life is 1 to 3 weeks.